2020
DOI: 10.3365/kjmm.2020.58.5.348
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Transport Properties of <i>n</i>-type InSe by Sn doping

Abstract: Layered post transition metal chalcogenides such as SnSe, SnSe<sub>2</sub>, In<sub>2</sub>Se<sub>3</sub>, and In<sub>4</sub>Se<sub>3</sub> have attracted attention as promising thermoelectric materials due to their intrinsically low lattice thermal conductivities. Recently, <i>n</i>-type indium selenide (InSe) based materials have also been suggested as good candidates for thermoelectric materials by optimizing their electrical properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Among these materials, InSe has a high S in the range of 600-1000 mV K À1 and a k tot in the range of 1-4 W m À1 K À1 . [13][14][15] However, InSe has a band gap of B1.25 eV, which leads to a very low carrier concentration of 10 13 -10 14 cm À3 . 13,15,16 Thus, one strategy to improve the zT of InSe is doping to increase the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these materials, InSe has a high S in the range of 600-1000 mV K À1 and a k tot in the range of 1-4 W m À1 K À1 . [13][14][15] However, InSe has a band gap of B1.25 eV, which leads to a very low carrier concentration of 10 13 -10 14 cm À3 . 13,15,16 Thus, one strategy to improve the zT of InSe is doping to increase the carrier concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] However, InSe has a band gap of B1.25 eV, which leads to a very low carrier concentration of 10 13 -10 14 cm À3 . 13,15,16 Thus, one strategy to improve the zT of InSe is doping to increase the carrier concentration. Choo et al reported that doping Sn in InSe increased the zT at 800 K to 0.14 by increasing the carrier concentration and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, high photoresponsivity, [ 16 ] photoconductivity, photovoltaic effect, [ 17 ] and thermoelectric effect [ 18 ] have been reported in InSe‐based photodetectors and phototransistors. Despite InSe as a benchmark 2D semiconductor having been researched widely, however, a detailed study of the PPC effect and relevant mechanism on the photoresponse of InSe‐based photodetectors is still not available.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous results found that InSe owns very low carrier concentration around ∼3.2 × 10 13 cm –3 at room temperature that largely restricts its thermoelectric performance. [ 22,23 ] Thus, both anion (Si and Sn) doping [ 22–25 ] and citation (Te) alloying [ 26 ] are conducted to optimize the carrier concentration in InSe, but the increase of carrier concentration is limited. Noticeably, the theoretical calculation results indicate that a maximum ZT of ∼0.65 can be achieved at 800 K with optimal carrier concentration.…”
Section: Introductionmentioning
confidence: 99%